Risk factors for recurrent laryngeal nerve injury following thyroid surgery: a systematic review and meta-analysis - Yang, Xiang; Ouyang, Wuzhou; Ma, Peng (Frontiers in Surgery, 2026)
BackgroundRecurrent laryngeal nerve injury is one of the most common and severe complications in thyroid surgery, potentially leading to postoperative hoarseness, dysphagia, or even airway obstruction. Although numerous studies have investigated its risk factors, findings remain inconsistent. This systematic review and meta-analysis aim to synthesize existing evidence and explore risk factors for recurrent laryngeal nerve injury following thyroid surgery.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library databases from their inception to October 1, 2025, to identify observational studies and randomized controlled trials investigating risk factors for recurrent laryngeal nerve injury following thyroid surgery. Two researchers independently performed literature screening, data extraction, and quality assessment using the Newcastle–Ottawa Scale (NOS). Stata 15 software was used to calculate pooled odds ratios (OR) and 95% confidence intervals (CI).ResultsA total of 20 articles(N = 108,343) included, meta-analysis results suggest that older age [OR = 1.45, 95% CI (1.26, 1.66)], Female [OR = 1.15, 95% CI (1.03, 1.28)], extended thyroidectomy [OR = 1.65, 95% CI (1.20, 2.27)], node dissection [OR = 2.28, 95% CI (1.67, 3.09)],reoperation [OR = 2.16, 95% CI (1.86, 2.50)], retrosternal goitre [OR = 2.85, 95% CI (1.87, 4.35)], lack of neuromonitoring [OR = 1.64, 95% CI (1.31, 2.06)] may be associated with RLNI following thyroid surgery.ConclusionThis study indicates that older age, female gender, extended thyroidectomy, lymph node dissection, reoperation, retrosternal goiter, and absence of nerve monitoring mya be independent risk factors for recurrent laryngeal nerve injury following thyroid surgery.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251106124, identifier CRD420251106124.